Candida–streptococcal interactions in biofilm-associated oral diseases - Koo, Hyun; Andes, David R.; Krysan, Damian J. (PLoS pathogens, 2018)
[...]these mannoprotein-deficient mutants developed poor mixed-species biofilms with S. mutans, showed reduced EPS α-glucans content, and reduced microbial carriage on teeth in vivo [18]. [...]the organisms enhance the carriage of cariogenic pathogens, biofilm accumulation, and acid production, promoting a localized and persistent acidogenic–aciduric microenvironment that potentiates demineralization of tooth enamel and may explain the synergistic enhancement of caries severity. Paradoxically, farnesol produced by C. albicans, which stimulates S. mutans growth and gtfB expression at low concentrations (25–50 μM), disrupts bacterial growth at high concentrations (>100 μM) [27]. [...]a tightly regulated cooperative and antagonistic balance through stimulus-inhibition mechanisms appears to mediate bacterial–fungal coexistence and survival within biofilms, which can become synergistic when conditions are conducive for disease (Fig 2). Elucidating how bacterial–fungal interactions occur spatiotemporally (cooperative, competitive, or both simultaneously) to mediate symbiotic, antagonistic, or synergistic states may shed new light into the pathogenic mechanisms and identify more effective therapeutic targets. Since cross-kingdom biofilms exist throughout the gastrointestinal tract, principles and molecules that emerge from these studies may lead to novel approaches to prevent and eradicate other intractable polymicrobial biofilms at various clinical niches.